Haemodynamics during cycling and long-distance running: a clue to footstrike haemolysis in Indian athltes - Janakiraman, K.; Shenoy, S.; Singh Sandhu, J. (Comparative Exercise Physiology, 2010)
Foot impact force during running has been suggested as one of the important causes of haemolysis in runners. However, intravascular haemolysis has also been reported among athletes involved in sports in which foot impact does not occur. The purpose of our study was to analyse intravascular haemolysis in athletes during running and compare it with cycling. Twenty male long- and middle-distance runners volunteered to participate in this study. They were divided into two groups (group 1: running and group 2: cycling), with 10 participants in each group. Each athlete completed 1 h of running or cycling at their calculated target heart rate (60-70%). Venous blood samples were collected before and immediately after the running and cycling protocols. Unconjugated bilirubin (UBR; P < 0.01) and lactate dehydrogenase (LDH; P <0.05) levels were increased significantly after running, indicating the occurrence of haemolysis in this group of athletes. A significant variation was observed in the mean values of haematological variables between post-run (UBR: 1.40 ± 0.29, LDH: 225 ± 69.13, haemoglobin (Hb): 11 ± 1.09) and pre-run (UBR: 0.88 ± 0.31, LDH: 183 ± 40.42, Hb: 12.10 ± 1.19) during the running protocol. No significant differences in haematological variables were found between athletes who did cycling and non-exercising group participants. Our results indicate that intravascular haemolysis occurred significantly during running when compared with cycling. Hence, we conclude that the mechanical trauma due to footstrike is the major cause of intravascular haemolysis during running.